A Study of Site Planning Integrated With Sustainable Stormwater Management in The Scale of Building -Comparative Analysis Utilizing 3D Measurement Technology Part2- - Tanaka, Tomoaki; Shimazaki, Hikaru (MAJ - Malaysia Architectural Journal, 2025)
This paper is the continuation of the previous paper, and thus the background of the study is shared. Reflecting the recent social needs, site planning integrated with sustainable stormwater management in the scale of building and district will become increasingly important. In this study, we focused on the scale of building. We conducted surveys using 3D measurement technology, targeting two types in the scale of building: a case where sustainable stormwater management has been prepared, Miyoshi Civic Hall Kiriri, and a case where the sustainable stormwater management was not sufficiently prepared, the Kawasaki City Museum. By analyzing and comparing the 3D data obtained from the surveys in the two cases, we aimed to examine relatively the effectiveness of stormwater management and damage by identifying the relationship between topographical features and the risks caused by them. First, for the Damaged case, we produced a 3D section of the damaged area and verified the relationship between the damage and the topography. Next, we verified the effectiveness of sustainable stormwater management for the Prepared case by following the same procedure. Then, we compared the two cases and examined how site planning integrated with sustainable stormwater management can be effective in the scale of building. Furthermore, we discussed the benefits and advantages in the two scales and examined the role of site planning integrated with sustainable stormwater management.